2020
DOI: 10.2147/opth.s245192
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of Time Exposed to Outdoor Light for Myopia Prevalence and Progression: A Literature Review</p>

Abstract: The development of myopia as a refractive disorder seems to hold multifactorial causes. Among others, increased time exposed to natural light outdoors is regarded as possible effective preventive measure against myopia development. The objective of this review is to analyse and summarize the evidence investigating the association between time outdoors and myopia prevalence and progression. Methods: A review, restricted to articles published in the last ten years, was conducted. The literature search for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 40 publications
2
47
0
2
Order By: Relevance
“…There is enough evidence about how children that spend more time outdoors [ 33 ] and less time doing near work activities [ 34 ] have less risk of developing myopia than those who do the opposite. The same conclusions have been found in previous studies in Spain [ 7 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is enough evidence about how children that spend more time outdoors [ 33 ] and less time doing near work activities [ 34 ] have less risk of developing myopia than those who do the opposite. The same conclusions have been found in previous studies in Spain [ 7 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…No interventions in decreasing nearwork have been validated in controlled trials. Strong evidence has been accumulated for time spent outdoors (principally lighting levels) decreasing the prevalence and progression of myopia, 16 19 possibly owing to dopamine release, decreasing the impact of other risk factors such as parental myopia 20 and higher levels of nearwork. 21 School-based intervention trials have shown that an increase in time outdoors of 40 to 80 minutes per day produces a significant decrease in the incidence of myopia.…”
Section: Environmental Modificationmentioning
confidence: 99%
“…Advising on maximizing time spent outdoors is good for all children's general mental health 35 as well as decreasing the incidence and progression of myopia, 16 19 especially in winter when myopic progression is greater. 36 However, as identified elsewhere in this article, this factor will have a limited effect on decreasing the incidence of myopia or its progression in those who are already myopic owing to societal factors.…”
Section: An Evidence-based Clinical Approachmentioning
confidence: 99%
“…Dentro de la gran mayoría de los artículos revisados, la medida de prevención que más aparecía era el incremento del tiempo al aire libre; el cual fue considerado como la mejor estrategia para la prevención y progresión de la miopía (11,19,28), no solo por su impacto en la miopía, sino que también va alineado con cambios en el estilo de vida de la población que resultan benéficos para la salud mental, cardiovascular, entre otras. En una revisión de literatura realizada en suiza (31) se halló que la mayoría de los estudios encotraron una asosiación inversa entre el tiempo al aire libre y la incidencia/prevalencia de la miopía. Esta información se puede corroborar con otros estudios, como aquel realizado en 1'060 925 estudiantes entre los 7 y 18 años de edad de 1305 escuelas primarias y secundarias en 11 distritos de ciudad de Wenzhou, provincia de Zhejiang, China (32), en donde se encontró que el tiempo que los estudiantes pasaban en línea estaba directamente relacionado con el incremento de la incidencia de la miopía (HR, 1.14; 95% CI, 1.07-1.22; P=3.39 x10-5 ) y su progresión ([SE]; B= 0.0188; P= 0.022), mientras que el tiempo al aire libre estaba asociado negativamente al incremento de la incidencia de miopía (HR, 0.91; 95% CI, 0.85-0.97; P= 0.021) y su progresión (SE; B=-0.0189; P=0.039).…”
Section: Prevención Primariaunclassified